Recovery of phenolic compounds from Eucalyptus wood wastes using ethanol-salt-based aqueous two-phase systems - Xavier,Lucía (Universidad del Bío-Bío, 2017)
In this work the partition behavior of phenols using ethanol-salt-based aqueous two phase systems (ATPS) was evaluated. The aim was the recovery of phenolic compounds with antioxidant capacity from eucalyptus wood industrial wastes. Experiments were planned to study the influence of several parameters on phenols partition, including type of inorganic salt (ammonium sulphate, a mixture of monopotassium phosphate and potassium diphosphate and potassium diphosphate), tie-lie lenght (TLL), volume ratio (Vr), settlement time and temperature. Phenols could be recovered preferently from the top or bottom phases depending on the salt used. It was demostrated that tie-lie lenght, volume ratio and temperature had influence on phenols partition. The highest total phenols yield 5,36 mg gallic acid equivalent (100 mg oven dried wood)-1 and FRAP antioxidant activity, 20 mmol AAE (100 g oven dried wood)-1, was obtained using ATPS formed by 40,6% (w/w) ethanol and 12% (w/w) of ammonium sulphate at 65°C. Analysis of the extract by RP-HPLC-ESI-TOF confirmed the presence of the phenolic compounds with potential antioxidant activity, namely, ellagic acid, myricetin 3-O-rhamnoside and quercetin 3-glucoside.